Active Membership in Indonesian National Health Insurance: A District Level Analysis - Asmaripa Ainy; Pujiyanto Pujiyanto (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: The Indonesian National Health Insurance (JKN) program in Indonesia has played an important role in providing access to health services for the community. Active membership is a key element in the development of the JKN program in Indonesia. High levels of active membership ensure financial stability, expanded coverage, and improved access to healthcare services. However, active membership in the program remains a challenge, with membership rates varying across regions. The purpose of this study was to analyze active membership and the factors influencing it at the district level. Methods: This study used a cross-sectional design. Secondary data were sourced from the provincial central bureau of statistics in Indonesia and data from system monitoring of the national social security council in 2023. Data analysis was conducted at the district level with a sample size of 479 districts and municipalities. Robust multiple linear regression analysis was employed to assess the influence between literacy, employment, illness history, household expenditure, and active JKN membership. Results: Findings based on cross-sectional data indicate that literacy and employment positively affect active JKN membership, while household expenditure has a negative effect; the illness history variable is not significant. Despite the model's overall significance (Prob > F = 0.00), it explains only 8.47% of the variation in JKN active membership (R-squared = 0.08). Conclusion: Socioeconomic variables such as literacy, employment, and household expenditure are essential in developing JKN membership policies. Educational programs to raise health insurance awareness, along with policy interventions aimed at improving literacy, employment stability, and people's economic well-being, can contribute to increased membership in JKN.